Gravesend - Swensen, Cole, 1955- (New California poetry., 2012)
Gravesend, which takes its name from the English town at the mouth of the Thames, revisits the genre of the ghost story and, through fragmentation, juxtaposition, and allusion, powerfully summons the uncanny, the spectral presence. Cole Swensen delves into ancient fables, the Bible, medieval records, Victorian ghost stories, contemporary interviews, and more to explore the effects of the ghostly on our daily lives, at times returning to the notion of "gravesend," implicitly asking if all ends in the grave or if death itself has an end. Swensen's focus on language shapes these visitations--glimp.